Post-merger performance of Selected Acquiring companies in India - Kaushik, Silky; Chauhan, Narendra Singh (International Journal of Psychosocial Rehabilitation, 2020)
In the present scenario, mergers and acquisitions (M&A) are seen as an important tool for corporate restructuring and value creation. It allows companies to expand their horizons, reduce business risks, explore new markets and geographic areas, thereby boosting profits and gaining competitive advantage. The goal of this research is to analyze the effect of fusions on the operational and financial performance of selected Indian companies analyzing different financial ratios of the sample of companies listed on bse / nse. For this purpose, for companies, three years of pre-and post-analysis has been done. The data is obtained from company annual reports.